EVALUASI RETURN DAN RISK ADJUSTED PERFORMANCE PORTOFOLIO VALUE VERSUS GLAMOUR PADA PASAR MODAL INDONESIA - Reza Pahlevi, Novan; Arfianto, Erman Denny (Faculty of Economics and Business Diponegoro University, 2015)
Further studies have consistently found problems with efficient market hypothesis by Fama. Underpriced stocks based on some form(s) of fundamental analysis can produce abnormal return in the major capital market in the world. This phenomenon called market anomalies. This research aim to determine whether value portfolio outperform glamour portfolio and to evaluate risk-adjusted performance between value and glamour stocks. Sample of this study used companies listed on LQ 45 during 2009-2013 periode. The portofolio formation based on consistent earner strategy (Elze, 2010) which is combination between PER & ROE and DY & ROE. After portfolio formation on 0MO, 3M0, 6MO, and 12MO, ANOVA test will be performed to determine the difference in returns and risk-adjusted performance for each portfolio formation. The results on this study found that there is no difference return and risk-adjusted performance between value and glamour portofolio during 2009-2013 at Indonesia Stocks Exchange.